Efficacy evaluation of Veeralin LN, a PBO-incorporated alpha-cypermethrin long-lasting insecticidal net against Anopheles culicifacies in experimental huts in Odisha State - Gunasekaran Kasinathan; Sudhansu Sekhar Sahu; Nallan Krishnamoorthy; Mohammed Mustafa Baig; Sonia Thankachy; Smrutidhara Dash; Swaminathan Subramanian; Purushothaman Jambulingam (Malaria Journal, 2020)
Abstract Background The success of malaria control using long-lasting insecticidal nets (LLINs) is threatened by pyrethroid resistance developed by the malaria vectors, worldwide. To combat the resistance, synergist piperonyl butoxide (PBO) incorporated LLINs is one of the available options. In the current phase II hut trial, the efficacy of Veeralin®LN (an alpha-cypermethrin and PBO-incorporated net) was evaluated against Anopheles culicifacies, a pyrethroid resistant malaria vector. Methods The performance of Veeralin®LN was compared with MAGNet®LN and untreated net in reducing the entry, induced exit, mortality and blood feeding inhibition of target vector species. Results The performance of Veeralin was equal to MAGNet in terms of reducing hut entry, inhibiting blood feeding and inducing exophily, and with regard to causing mortality Veeralin was better than MAGNet. When compared to untreated net, a significant reduction in hut entry and blood feeding and an increase in exophily and mortality were observed with Veeralin. In cone bioassays, unwashed Veeralin caused > 80% mortality of An. culicifacies. Conclusions Veeralin performed equal to (entry, exit, feeding) or better than (mortality in huts and cone bioassays) MAGNet and could be an effective tool against pyrethroid resistant malaria vectors.